Effect of In-Vitro Alpha Lipoic Acid Addition on Spermatozoa Motility in Sperm Preparation Process - Buanayuda, Gede Wira; Lunardhi, Hamdani; Mansur, Indra Gusti (Folia Medica Indonesiana, 2019)
Infertility is a problem for husband and wife, in the last 20 years the number of infertile couples has tended to increase by around 6.5 million pairs. The infertile couple can use the intrauterine insemination method to obtain offspring if a conventional method approach cannot be performed. Insemination requires a sperm preparation stage in which there are centrifugation and resuspension procedures that tend to produce excess reactive oxygen species (ROS). Excessive ROS will damage the motility of the spermatozoa. This study aims to prove the addition of alpha lipoic acid (ALA) as an antioxidant in the process of sperm preparation to improve and maintain better sperm motility. This research is a laboratory study with an experimental research design. The sample consisted of 10 infertile men who visited the Andrology section of the Sayyidah Jakarta Mother and Child Hospital (RSIA), where each ejaculate from the patient would be divided into 3 groups namely (k1) fresh semen as a control group, (k2) sperm preparation group without ALA, (k3) group of sperm preparation with the addition of ALA. The motility of spermatozoa was observed with the WHO 1999 method for 4 hours in units of percent. Progressive motility in k3 (47.95 ± 3.617) was higher than in k2 (38.05 ± 3.278) statistically significantly different after 3 hours of observation (p<0.0001). Progressive motility in k3 (78.8 ± 5.841) was higher than k1 (56.55 ± 7.511) from the initial observation (p <0.0001). The progressive motility of k2 (76.05 ± 6.768) was higher than k1 (56.55 ± 7.511) from the start of the observation (0.0001). It can be concluded that the addition of ALA in the sperm preparation process increases and maintains progressive motility that is better than sperm preparation without ALA addition after 3 hours of observation.